Analysis Of Factors Influencing Satisfaction With Using The Mobile Lapor Application In Indonesia - Theresa Karyn Wijaya; Nilo Legowo (International Journal of Advanced Science and Computer Applications, 2024)
Through this fairly rapid digital growth, the Indonesian government sees opportunities in providing digital-based services through mobile-based applications and websites called LAPOR (People's Online Aspiration and Complaints Service) as a means for the Indonesian people to provide complaints, aspirations or requests for information to agencies. governance is aimed at only 1 platform that integrates with each other. However, unfortunately the mobile application service LAPOR (People's Online Aspiration and Complaints Service) is still unable to satisfy the needs and desires of users in using all the services provided. This is proven by the assessment and comments column of the REPORT mobile application on Playstore and AppStore. Therefore, this research was carried out to determine the factors that influence user satisfaction in using the LAPOR mobile application which was assessed or processed into 5 research variables including Ease of Use, Security Privacy, Attitude Toward Using, System Quality and User Satisfaction